NATO at 60 - Bebler, Anton (IOS Press, 2013)
As we reach its 60th anniversary, NATO – a security alliance of 28 countries from North America and Europe – remains the principal security instrument of the transatlantic community and the expression of its common democratic values. However, the NATO today is no longer that of 1949. After the collapse of Communism and the Soviet Union, NATO had to reinvent itself politically for the initial challenges of the post-Cold War era. In the space of a decade NATO successfully transformed itself from a North American-Western European Alliance focused exclusively on territorial defence into a pan-European institution with new members stretching from the Baltic to the Black Sea. NATO’s missions have changed and its structures have been reformed accordingly. It has had to adapt to the changing world and changing threats such as terrorism, the proliferation of weapons of mass destruction, transnational trafficking, piracy, cyber attacks and climate change. Sixty years after its foundation NATO has not become rusty or outdated. On the contrary, in the new security environment its role has increased. NATO remains the pre-eminent institutional framework for the USA, Canada and Europe – not just to consult together, but also to act together. NATO’s key stabilising role in the Balkans and, more recently, in Afghanistan; its role in fighting terrorism; and the continuing interest on the part of several nations in joining NATO, all demonstrate that the Alliance is very much in demand. "The Post-Cold War Enlargement and the Alliance’s Future" reflects upon NATO’s achievements and setbacks at the time that explores the challenges that lie ahead in the future of the most successful military Alliance of the modern Euro-Atlantic history and beyond. This book is a must-have for those interested in international relations, global security and defence issues.